Fabrication of Nanogel for Topical Drug Delivery of Montelukast - Pandey, Trapti; Sharma, Neeraj; Gupta, Naveen; Rajput, Dharmendra; Tripathi, Kuldeep (Asian Journal of Pharmaceutical Research and Development, 2022)
A novel nanocrystal system of montelukast (MTK) was designed to improve the transdermal delivery, while ensuring chemical stability of the labile compound. MTK nanocrystal Nanogel was fabricated using using nano dispersion method (Modified emulsification diffusion method). In the pre-formulation study, there was not any physicochemical interaction between drug and polymer had been evaluated by FTIR. The melting point was found to be 134- 137 0C. It is freely soluble in Cyclohexane & butanol ratio and water. The standard curve of ondansetron had been prepared by Cycloheaxxane & butanol (7:3). Montelukast nanogel were prepared by nanodispersion method. Formulations of different drug ratio were optimized with selected parameters like particle size, PDI, Zeta potential, entrapment efficiency, clarity test. pH test of gel, viscosity and gelation temperature. Drug release studies were performed by dialysis bag diffusion technique at a temperature (37°C). The study was continued for 24 hours till. The maximum amount of drug montelukast release 87% within 24 hr. The study was monitored at 37°C. Preparation, characterization and drug release study of montelukast loaded nanogel. This approach of montelukast loaded nanogel with chitosan as the polymer is quite successfully developed.